2019
DOI: 10.36787/jsi.v2i1.57
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Pertanahan di Lingkungan Kantor Wilayah Badan Pertanahan Nasional Provinsi Jawa Barat

Abstract: Tujuan penelitian ini adalah: 1) Mengungkap deskripsi motivasi kerja dan kinerja karyawan Kantor Pertanahan Daerah Jawa Barat, 2) menguji hipotesis hubungan dan pengaruh antara motivasi kerja dan kinerja karyawan. Jenis penelitian ini adalah deskriptif. dan penelitian verifikatif. Metode yang digunakan dalam penelitian ini adalah metode survei. Ukuran sampel adalah 219 pegawai Kantor Pertanahan Regional Jawa Barat yang diambil sampelnya dengan metode proportional stratified random sampling. Data yang digunakan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
4
0
0
1
Order By: Relevance
“…This means incentives, work motivation, incentives, it will improve employee performance. This is in line with research, Iha Haryani Hatta, (2015) Mangasa Panjaitan, (2015) which shows that the results show support for a significant influence between incentives, motivation and job satisfaction on employee performance. So it can be concluded that the hypothesis of this study, namely incentives, motivation and job satisfaction simultaneously have a significant effect on the performance of employees of the West Air Hangat Subdistrict Office has been proven.…”
Section: The Effect Of Incentives Motivation Job Satisfaction On the ...supporting
confidence: 92%
See 2 more Smart Citations
“…This means incentives, work motivation, incentives, it will improve employee performance. This is in line with research, Iha Haryani Hatta, (2015) Mangasa Panjaitan, (2015) which shows that the results show support for a significant influence between incentives, motivation and job satisfaction on employee performance. So it can be concluded that the hypothesis of this study, namely incentives, motivation and job satisfaction simultaneously have a significant effect on the performance of employees of the West Air Hangat Subdistrict Office has been proven.…”
Section: The Effect Of Incentives Motivation Job Satisfaction On the ...supporting
confidence: 92%
“…that motivation has an influence on the performance of employees at the North Samarinda Sub-district Office. This result is also supported by the results of research from Mangasa Panjaitan, (2015) that the effect of incentives and work motivation partially on employee performance at the North Sumatra Provincial Agriculture Office. This means that there is a positive relationship between motivation and performance, if motivation is good, it will improve the performance of West Air Hangat Subdistrict Office Employees.…”
Section: Test F (Simultaneous Test)supporting
confidence: 60%
See 1 more Smart Citation
“…This shows that hypothesis 3 is rejected, meaning that job satisfaction has no positive effect on performance; but on the contrary job satisfaction has a negative effect. This is in accordance with Abidin (2010) which states job satisfaction has no positive effect on performance.…”
Section: The Effect Of Job Satisfaction On Performancesupporting
confidence: 91%
“…Adanya inkonsistensi hasil penelitian terdahulu pada Tabel 3., menjadi celah untuk dilakukan penelitian kembali dan diperlukan adanya variabel lain yang bertindak sebagai variabel moderator. Variabel lain yang mempengaruhi kinerja salah satunya adalah motivasi kerja seperti dibuktikan pada penelitian Panjaitan (2019), Lusri dan Siagian (2017), serta Nurhayati (2017). Motivasi kerja adalah sikap dan nilai yang mampu memberikan kekuatan untuk mendorong individu bertingkah laku dalam mencapai tujuan (Nurhayati, 2017).…”
unclassified